Towards sustainable livelihoods in the Tanzanian informal economy: Facilitating inclusion, organization, and rights for street vendors - Ilona Steiler; Chediel Nyirenda (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2021)
In spite of having some intensive national strategies to address poverty, Tanzania lacks a coherent national strategy to ensure sustainable livelihoods for those working in its informal economy, of which street vending is an important sector. Based on qualitative, in-depth data collected through interviews and participant observation between 2014 and 2019, our research scrutinizes how recent policies are improving the sustainable livelihoods of street vendors. We suggest two related foci for research and policy intervention. Firstly, the considerable diversity among street vendors regarding employment relation, gender, age, capital, and assets must be taken into account to design inclusive and sustainable policies. Secondly, the current policies and issuing of identification cards offer new opportunities for vendors to organize and claim their rights, but they need to be unambiguously enshrined in law. This will improve smooth and fair revenue collection and, importantly, street vendor organization and representation in decision-making processes at various levels of government.
Keywords: D78; J46; J83; O17; 330; Tanzania; street vending; sustainable livelihoods; street vendor organization; informal economy